Feminism, peer culture, gender and race: a reflection on being a black girl - Raíssa Francisco Santos; Edna Rodrigues Araújo Rossetto (Universidade Federal de Santa Catarina, 2018)
The objective of this article is to discuss studies on the production of children's cultures, highlighting the importance of the role of black girls in pre-school and show how affected they are by racist and sexist relationships in pre-school, legitimized by the capitalist system. From the studies of Kimberly Crenshaw (1989), Helena Hirata (2014), Angela Davis (1982), Lélia Gonzales (1984) and Fernandes (1989) we will provide the historical scope for the subject as inter-relations and processes of the interaction between power relations and categories such as class, race, gender and identity. Racial struggle, a class struggle, and gender equality must all come together in the struggle for the transformation of society.